Evaluating the efficacy of virtual prenatal counseling for genitourinary anomalies - Moran, George W.; Schoenfeld, Daniel; Movassaghi, Miyad; Finkelstein, Julia B. (Frontiers in Urology, 2022)
Introduction and Objectives: The standardization of fetal sonography has enabled early detection of genitourinary anomalies and referral for prenatal counseling with pediatric urologists. Prenatal urologic consultation can determine the need for antenatal and postnatal intervention, assuage parental anxiety, and establish continuity of care. The COVID-19 pandemic led to a significant increase in virtual visits (VVs). Our aim was to characterize a cohort of patients who underwent prenatal VVs with pediatric urologists and to assess adherence to prenatal recommendations for neonatal urologic care. Materials and Methods: Data were collected through retrospective chart review of all patients receiving prenatal virtual consultation for genitourinary anomalies at our institution from July 1, 2020 to September 30, 2021. Data collected include maternal and gestational age at the time of prenatal imaging and VV, diagnosis of the fetus and neonate, and adherence to pediatric urological recommendations. Results: During the study period, there were 70 prenatal VVs for 69 singleton and 1 twin gestation. 84 prenatal genitourinary diagnoses were made in these 71 cases. Of the 56/71 children known to have been born by the time of analysis, there are 63 postnatal genitourinary diagnoses. Postnatal diagnoses were consistent (38/56, 68%) or partially consistent (16/56, 29%) with prenatal diagnoses in 54/56 neonates (96%). There was 100% adherence to the postnatal imaging and antibiotic recommendations. One patient failed to attend the postnatal visit and one patient is due for repeat postnatal imaging to determine the necessity of follow-up. Conclusions: Prenatal VVs promoted effective counseling of genitourinary anomalies and were associated with impressive postnatal adherence to prenatal recommendations. This is, to our knowledge, the first study to assess the impact of prenatal virtual pediatric urological consultation on postnatal adherence to prenatal recommendations. Future study will benefit from survey of the patient VV experience and evaluation of the relative merits of virtual versus in-person prenatal visits in a prospective, randomized fashion.